72.5k views
4 votes
-5x+y=6
-3x+6y=-12
Solving systems of equations by substitution

User Gordy
by
5.3k points

1 Answer

4 votes

if you isolate y in the top equation to get y=5x+6 then you can substiture y for 5x+6 in the bottom equation because thats what y equals

as of now you have -3x+6(5x+6)=-12 but if you use the distrubite property you would get -3x+30x+36=-12

then if you subtract 36 from both sides you would get -3x+30x=-48 then combine like terms to get 27x=-48 then divide both sides by 27 to get
x=(-48)/(27) or x≈1.8

User Brian Henry
by
5.8k points